A companion to media fandom and fan studies - Booth, Paul 1981- (Hoboken, New Jersey Wiley Blackwell, 2018)
"A Companion to Media Fandom and Fan Studies offers scholars and fans an accessible and engaging resource for understanding the rapidly expanding field of fan studies. International in scope and written by a team that includes many major scholars, this volume features over thirty especially-commissioned essays on a variety of topics, which together provide an unparalleled overview of this fast-growing field.

Separated into five sections—Histories, Genealogies, Methodologies; Fan Practices; Fandom and Cultural Studies; Digital Fandom; and The Future of Fan Studies—the book synthesizes literature surrounding important theories, debates, and issues within the field of fan studies. It also traces and explains the social, historical, political, commercial, ethical, and creative dimensions of fandom and fan studies. Exploring both the historical and the contemporary fan situation, the volume presents fandom and fan studies as models of 21st century production and consumption, and identifies the emergent trends in this unique field of study."
Includes bibliographical references and index.
Keywords: Fans (Persons); Subculture; Mass media -- Social aspects